Comparison of diode laser with maleic acid and ethylenediaminetetraacetic acid on smear layer removal from root canals: A scanning electron microscope study - Shahnaz Nabi; Riyaz Farooq (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of the study was to evaluate the effect of diode laser with maleic acid andethylenediaminetetraacetic acid (EDTA) on smear layer removal from root canals. Materials and Methods: A total of 160 mandibular premolars were decoronated to the working length of 12 mm and prepared with ProTaper gold rotary files up to size F3. Group 1 canals were irrigated with 1 ml of 17% EDTA, followed by 3 ml of 3% sodium hypochlorite (NaOCl). Group 2 canals were initially irrigated with 0.8 ml of 17% EDTA, the remaining 0.2 ml was used to fill the root canals, and diode laser application was done. Group 3 canals were irrigated with 1 ml of 7% maleic acid, followed by 3 ml of 3% NaOCl. Group 4 canals were irrigated with 0.8 ml of maleic acid and remaining 0.2 ml was used to fill canal (total 1 ml) and activated by diode laser, followed by 3 ml of 3% NaOCl. Scanning electron microscope examination of the canals was done for the remaining smear layer at the coronal middle and apical third levels. Results: Maleic acid with and without diode laser had the least smear layer scores. Conclusion: Diode laser with maleic acid performed significantly better than EDTA.